2018
DOI: 10.1051/matecconf/201823401004
|View full text |Cite
|
Sign up to set email alerts
|

Challenging low Reynolds - SWT blade aerodynamics

Abstract: One of the main issues related to the design and development of small wind turbines (SWTs) is the low Reynolds number. Operation in the transitory regime makes the rotor aerodynamic analysis a challenging task. Project GUST (Generative Urban Small Turbine) realized currently at the Institute of Turbomachinery (Lodz University of Technology, Poland) is devoted to the development of SWT (D = 1.6 m) for low-Reynolds number (low wind speed) flow conditions. The emphasis is on the blade design, aiming at improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The authors reported that the C p vs. λ curves's dependence on Reynold's number was caused by variations in the rotor's aerodynamic lift and drag coefficients with the Reynolds number. Another experimental study carried out by Kadrowski et al reveals that higher Reynolds numbers allow the turbine to reach higher maximum power coefficients C p,max but at lower optimum tip-speed ratios λ opt [9]. Similar studies have also been conducted with micro-scale vertical axis wind turbines [10,11].…”
Section: Introductionmentioning
confidence: 78%
“…The authors reported that the C p vs. λ curves's dependence on Reynold's number was caused by variations in the rotor's aerodynamic lift and drag coefficients with the Reynolds number. Another experimental study carried out by Kadrowski et al reveals that higher Reynolds numbers allow the turbine to reach higher maximum power coefficients C p,max but at lower optimum tip-speed ratios λ opt [9]. Similar studies have also been conducted with micro-scale vertical axis wind turbines [10,11].…”
Section: Introductionmentioning
confidence: 78%
“…The gray patches indicate the 𝜆 ranges where the numerical solution is more problematic (see, e.g., [42,47]) due to the appearance of high angle of attacks (i.e., stall) at low tip speed ratios (high 𝛼, low 𝜆) and negative angle of attacks (nearly zero and negative 𝐶 𝐿 ) at high tip speed ratios (low 𝛼, high 𝜆). 𝐶 𝑃 strongly decreases when 𝐶 𝐿 ∕𝐶 𝐷 drops [48,49], so the analysis of these regions is not relevant under the steady-state conditions considered here.…”
Section: Rotor Designmentioning
confidence: 99%
“…This small wind turbine has a nominal power 350 W at a wind velocity of 8.4 m/s [20]. The blades are of variable chord and twist angle ( Figure 1) and are constructed upon NREL S826 and S834 airfoils [21]. The examined rotor radius R is equal to 0.8 m, which is the same as that used in experimental investigation used as a reference.…”
Section: Object Of the Studymentioning
confidence: 99%